2011
DOI: 10.18388/abp.2011_2295
|View full text |Cite
|
Sign up to set email alerts
|

Is MLC phosphorylation essential for the recovery from ROCK inhibition in glioma C6 cells?

Abstract: Inhibition of Rho-associated protein kinase (ROCK) activity in glioma C6 cells induces changes in actin cytoskeleton organization and cell morphology similar to those observed in other types of cells with inhibited RhoA/ROCK signaling pathway. We show that phosphorylation of myosin light chains (MLC) induced by P2Y₂ receptor stimulation in cells with blocked ROCK correlates in time with actin cytoskeleton reorganization, F-actin redistribution and stress fibers assembly followed by recovery of normal cell morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…With ROCK inhibition, MLC kinase-activated stress fibers are not assembled in the cell center [86]. The physiological function of actin cables at the periphery of the cell also appeared to differ from that of the central cables [67, 87, 88]. In mouse embryonic fibroblasts, FCs showed the same periodic localization as MLC kinase suggesting that early adhesion-site formation is designated by myosin-dependent retractions [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With ROCK inhibition, MLC kinase-activated stress fibers are not assembled in the cell center [86]. The physiological function of actin cables at the periphery of the cell also appeared to differ from that of the central cables [67, 87, 88]. In mouse embryonic fibroblasts, FCs showed the same periodic localization as MLC kinase suggesting that early adhesion-site formation is designated by myosin-dependent retractions [89].…”
Section: Discussionmentioning
confidence: 99%
“…In smooth muscle cells, ROCK activation stimulated contraction [62], while dominant-acting mutants of ROCK induced stress fibers and focal adhesions [6366]. Conversely, ROCK inhibition released stress fibers from their attachments to FCs [67]. …”
Section: Introductionmentioning
confidence: 99%
“…The obtained images were converted to 8‐bit tiff images. Next, an axonal length and cellular dimensions (i.e., length and width) were determined using LAS AF software (Leica Microsystems) equipped with all measurement tools . A mean value of eight different measurements was determined and a standard deviation was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Myosin II activation in these two cable systems is controlled by ROCK and MLCK through MLC phosphorylation. Also, the physiological function of peripheral actin cables in the cell appeared to differ from that of the central cables [193,216,217]. FCs in mouse embryonic fibroblasts showed the same periodic localization as MLCK suggesting that early adhesion-site formation is designated by myosin-dependent retractions [218].…”
Section: Actomyosin Contractility In Factor 7 Feature Formationmentioning
confidence: 97%
“…It has been observed that in smooth muscle cells, ROCK activation stimulated contraction [188], while dominant-acting mutants of ROCK induced stress fibers and focal adhesions [189][190][191][192]. Conversely, ROCK inhibition released stress fibers from their attachments to FCs [193].…”
Section: Fcsmentioning
confidence: 99%